Novel vocalizations are understood across cultures - ?wiek, Aleksandra; Fuchs, Susanne; Draxler, Christoph; Asu, Eva Liina; Dediu, Dan; Hiovain, Katri; Kawahara, Shigeto; Koutalidis, Sofia; Krifka, Manfred; Lippus, Pärtel; Lupyan, Gary; Oh, Grace E.; et al. (Nature Research, 2021)
Linguistic communication requires speakers to mutually agree on the meanings of words, but how does such a system first get off the ground? One solution is to rely on iconic gestures: visual signs whose form directly resembles or otherwise cues their meaning without any previously established correspondence. However, it is debated whether vocalizations could have played a similar role. We report the first extensive cross-cultural study investigating whether people from diverse linguistic backgrounds can understand novel vocalizations for a range of meanings. In two comprehension experiments, we tested whether vocalizations produced by English speakers could be understood by listeners from 28 languages from 12 language families. Listeners from each language were more accurate than chance at guessing the intended referent of the vocalizations for each of the meanings tested. Our findings challenge the often-cited idea that vocalizations have limited potential for iconic representation, demonstrating that in the absence of words people can use vocalizations to communicate a variety of meanings.
Keywords: Speech and Language Therapy; Across Cultures; Novel Vocalizations